Results of measurements of electric power characteristics in power supply systems of enterprises and organizations - А. V. Ded; S. P. Sikorskiy; P. S. Smirnov (Омский научный вестник)
The article shows the results of measurements of electrical energy quality and their analysis carried out. Measurements are carried out at characteristic points of control of distribution network of 0,4 kV of enterprises and organizations of different branches of economy. It has been found that the parameters of the supply voltage according to a series of parameters of more than 30% have deviations from the permissible standards set in the standards documents. It is confirmed that the main indicator having the largest percentage of deviation from the boundary values is the steady-state voltage deviation.